El nivel de colocaciones en la agencia principal de la cooperativa de ahorro y crédito Parroquia San Lorenzo Ltda. Período 2012 - 2016 - Espejo Chávez, Joel Arturo (2018)
This work aims to describe the evolution of the placements of the Lead Agency from the year 2012 until march 2018, the causes that provoked that they increase or decrease, and solutions, taking into account the economic theory, for explain your behavior. The present report consists of four chapters: The first chapter describes the context of the peruvian financial system, institutions that comprise it and regulate, cooperatives in the financial system, the creation and development of the Cooperative San Lorenzo, also, its mission, vision and values, organization, products and services. In addition, describes the General and specific functions as a credit analyst, as well as problems related to the work and the objectives of the report. The second chapter shows some theoretical concepts, theoretical tools of economy used in job performance, related to productivity within the institution; in addition to an idea of "what is a cooperative", types of classification that the Superintendencia de Banca, Seguros y Administradora de Fondo de Pensiones (SBS and AFP) indicates to take into account when a customer or partner can be or not a subject of credit. In the third chapter is carried out the analysis of the evolution of the index of placements of the lead agency of the Cooperativa San Lorenzo. Proposes solutions for an efficient part of the collaborators productivity. In the last chapter is a critical evaluation for vocational training at the school of Economics, proposed suggestions based on the experience gained to improve the curriculum of the school, so there is a complementarity between the theoretical and the practical academic teaching, which will bring greater knowledge and expertise to future professionals so that they develop their level of skills across the labour market.